THE RELATIONSHIP BETWEEN EMPLOYER BRANDING, CORPORATE REPUTATION, AND RECRUITMENT WEB ON INTENTION TO APPLY - Fenti Erlinda; Rini Safitri (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Research on intention to apply has been done before. Some of  the research that resulted in that the variables - variables that influence on intention to apply is employer branding , reputation of the company , the website recruitment , will be but the results of the study are contained inaccuracies which said that the reputation of the company and website recruitment no effect on intention to apply, so it needs to do research back to answer the formulation of the problems associated with the effect of employer branding, reputation of the company and website recruitment against intention to apply. The purpose of this study was to determine the effect of employer branding, company reputation, and website recruitment on intention to apply. The population in the study subjects was 102,290 people with a sample of respondents as many as 99 people. The method of determining the sample using simple random sampling method. Data collection in this study was carried out through observation, interviews, and questionnaires. The approach that is used in research this is the approach of quantitative, testing the hypothesis in research is using Partial Least Square (PLS) version 3.2.9. Results of the study show the employer branding and reputation of the company has influence positively and significantly to intention to apply, while the website recruitment has influence negatively and significantly against intention to apply.Keywords: employer branding, company reputation, website recruitment, intention to apply